Daily activity monitoring of an elderly Person for determining their wellness - Arshad, Atika; Khan, Sheroz; Midi, Nur Shahida; Alam, A. H. M. Zahirul; Ismail, Ahmad Fadzil; Tasnim, Rumana (Science Engineering Research Support Society, 2016)
The work carried out in this paper aims to present a model based on elderlies daily activities to determine their wellness status. A wellness function is delineated to estimate the health condition of the aged individuals while carrying out their day-to-day routine. The proposed model can also be used to monitor the mobility parameters, such as entry and exit of a room and bed occupy of an elderly. Simple sensors such as capacitive sensors are equipped into their homes to monitor their behaviour and identify their daily activities via non-contact means. The device will allow extracting daily behavioral patterns of the elderly is distressed, an alarm can be sent to a receiver unit. The cost effectiveness of the device will ultimately lower the total cost of wellness monitoring of an elderly person. A prototype of the device can be fabricated and broadly tested for extracting precise results.